A ubiquidade na comunicação e na aprendizagem : ressignificação das práticas pedagógicas no contexto da cibercultura - Mantovani, Ana Margô (2016)
This thesis aims to investigate how professors resignify their teaching practices in higher education, through ubiquitous learning and communication in the context of cyber culture. To understand this issue, we seek a theoretical framework that includes the "Biology of Knowledge", the "Love Biology" and the multi-referential approach. We included in this framework, the contemporary theoreticians who study the cyber culture and its impact on education and communication. This is a qualitative case study, consisting of a group of professors of a Higher Education Institution of the Private Network. Given the particularities of the case studied, we found one more reference in the research-training to broaden the understanding of the issues addressed here. The Discursive Textual Analysis is the method of interpretation of the professors’ narratives. In the context of this study, we found that the professors (a) incorporate, in their teaching practices, emerging communicational dynamics of cyber culture, through ubiquitous communication and dialogical relations established; (b) propose problematizing learning situations, building knowledge in a process of co-authorship, configuring a hybrid and ubiquitous living space where professors and students become coteachers and co-learners of this training process; (c) promote integration strategies of ubiquitous learning in formal education that involve curricular experiences in training, creating synergies between urban space and cyberspace, the school and the university; d) share knowledge in action-reflection that emerges from the formative experiences lived in different contexts, setting up study groups with research-training characteristics. We observe that a teacher training course needs to be thought from the perspective of an ecology of ubiquity, for the construction of training environments that allow the experience of selftraining processes, hetero-training and meta-training in living and coexisting with professors. We conclude that, to incorporate the potential of ubiquity in the processes of teaching and learning, it is necessary to establish a dialogical and multi (directional/dimensional) communication dynamics, based on interactivity, so that the educational process is congruent with the demands of contemporary times.